(untitled) (Dhaka University Journal of Biological Sciences, 2022)
An assessment was done to assess the intensity of rat eater and non-rat eaters’ species killed by the people during the rodent outbreaks in association with Melocanna baccifera bamboo flowering in the village of Basatlang, Neweden, Munlai, Mualpi and Ruma sadar market area of Ruma upazila of Bandarban district. The other objectives of the study were to support the future control of rodent outbreaks and conservation of wild animal species. A structured data sheet was used to record the hunted rat eater and non-rat eaters’ data from June 2009 to December 2012. Shannon-Wiener’s diversity index and Simpson’s diversity index were also calculated to assess the diversity of rat eaters and non-rat eater species. The study revealed that a total of 628 numbers of hunted rat eater and non-rat eater animals (average 14.60 numbers per month) recorded with 41 species. Of them, 12 species of mammals, 11 species of reptiles and 18 species of Aves. The overall hunted rat eater and non-rat eater diversity indices were 2.59 for Shannon-Wiener’s diversity index, and 0.82 for Simpson’s diversity index that indicate high species diversity. Irrawaddy squirrel, Tokay gecko, wild boar, deer and red-vented Bulbul were the top five hunted non-rat eater species. Domestic dog, monitor lizard, jungle cat, domestic cat and striped keelback snake were the top five rat eater species hunted by the people. Consumption and economic return were the main reasons for hunting the animals. These findings can be used to raise public awareness along with application of Wildlife (Conservation and Security) Act, 2012 to stop killing of rat eater and non-rat eater species during the rodent outbreaks and non-outbreaks period in the study areas, and elsewhere in Chattogram Hill Districts. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 465-477, 2022 (June)